The Implementation of Fiqh Principle in Islamic Financial Products: A Systematic Literature Review - Ni'mah, Nafisatu Roudlotin; Asmuni, Asmuni (University of Darussalam Gontor, 2024)
The fiqh rules aim to provide a foundation for all activities carried out by Muslims, including economic activities. Through the rules of fiqh, various contemporary economic problems can be solved by drawing a red thread from the arguments that have existed before. For example, the phenomenon of online buying and selling that is currently rife can be found by linking the arguments that can be used as a reference. This implementation must be done because, with it, Islamic economic activity will be easier to achieve its goals. The purpose of this study is to find out the application of the rules of fiqh in various Islamic financial products. The method used in this study is a systematic literature review by extracting several scientific journals related to the theme. The application of the rules of fiqh in various Islamic financial products has proven to be significant and has a positive impact from various economic sides. The application of the rules of fiqh makes all economic layers have a foundation in doing something so that it does not come out of the principles of Islamic sharia.